The determinant of the financial fraud of the village fund management - Fachrurrozie Fachrurrozie; Agus Wahyudin; Ahmad Nurkhin; Hasan Mukhibad; Kardiyem Kardiyem; Fadhilah Mahanani Saputri (University of Merdeka Malang, 2020)
We examine the relationship between compensation, morality, organizational ethical culture, and financial fraud. The respondents were fifty-two village officials in Weru Subdistrict, Central Java Sukoharjo District who were directly responsible for managing village funds. They were selected using a purposive sampling method. Data was collected by means of the questionnaire was distributed and then, the data were analyzed using Path analysis with WarpPLS software. We found that morality had a positive and significant effect on compensation and organizational ethical culture, as well as a negative and significant effect on financial fraud. Organizational ethical culture proved to have a negative and significant effect on financial fraud. Compensation does not have a significant effect on the ethical culture of the organization and financial fraud. The other result shows that the organizational ethical culture had proven to be a mediator of the relationship between morality and financial fraud. Meanwhile, there is no proven significant relationship between the suitability of compensation for financial fraud through the ethical culture of the organization. Also, the study confirmed that the morality and ethical culture of the organization are factors that can reduce the occurrence of financial fraud. Hence, the village government is expected to have better organizational morality and ethical culture.JEL Classification: G28, H83, M41 How to Cite: Fachrurrozie, Wahyudin, A., Nurkhin, A., Mukhibad, H., Kardiyem, Saputri,F. M. (2020). The determinant of the financial fraud of the village fund management. Jurnal Keuangan dan Perbankan, 24(1), 95-105.DOI: https://doi.org/10.26905/jkdp.v24i1.3576